Léon Stynen : A life of architecture 1899-1990 - De Caigny, Sofie, 1977-; Laureys, Dirk; Dujardin, Filip, 1971-; Dubois, Marc, 1950-; Floré, Fredie, 1974-; Avermaete, Tom, 1971-; Vlaams Architectuur Instituut, VAi / The Flemish Architecture Institute (Antwerpen : Vlaams Architectuurinstituut, 2018)
Few Belgian architects have left behind such a striking and diverse oeuvre as Léon Stynen (1899-1990). For more than 50 years, Stynen was active as an architect, urbanist and designer. He worked all over the country, but with a great love for his native city of Antwerp. In addition to the realization of this important architectural oeuvre, he also played a major role in the development of architecture education and architectural culture in Belgium. Every publication on Belgian architectural history asserts Stynen as one of the iconic architects of his generation.
Paperback in box
This book accompanies the exhibition Léon Stynen, Architect, organized from 12/10/2018 until 20/01/2019 by the Flanders Architecture Institute at deSingel international arts campus, Antwerp (BE)
Tentoonstelling, Antwerpen, deSingel, 12/10/2018 - 20/01/2019
Schenking Vlaams Architectuurinstituut
kunstcatalogus
Keywords: Stynen, Leon, -- 1899-1990.